READING COMPREHENSION QUESTIONS IN ENGLISH TEXTBOOK BASED ON BLOOM’S TAXONOMY FOR GRADE XII - Prasiska Oktaviani Gultom; Johannes Jefria Gultom (Universitas Negeri Medan, 2021)
This study aimed at identifying and analyzing the types and levels of questions available in the third grade of senior high school. The purpose of the analysis was to determine the distribution of the questions over the six levels of the new version of Bloom's Taxonomy of the cognitive domain. The sample of the study consisted of the English textbooks where the researcher analyzed (144) questions. The results revealed the following: for remembering - understanding (20%), analyzing - applying (55%) evaluating (15%) and creating (10%). The proportion of regulation by the ministry of education and culture shows remembering – understanding level is 20%, whereas in the distribution of cognitive domain in data analysis shows remembering – understanding is 70.7%, applying – analyzing is 55%, whereas in the distribution of cognitive domain in data analysis shows applying – analyzing is 21.4%, evaluating is 15%, whereas in the distribution of cognitive domain in data analysis shows evaluating is 2.4%, and creating 10%, whereas in the distribution of cognitive domain in data analysis shows creating is 5.5%. Based on the data above it clearly shows the significant differences between proportion of regulation by ministry of education and culture with the result of the data analysis in English textbook for third grade of senior high school is inappropriate with the regulation by ministry of education and culture.Keywords : English Textbook, Bloom’s Taxonomy, Reading Comprehension Question